New Zealand : Financial Sector Assessment Program: Technical Note-Stress Testing the Banking Sector and Systemic Risk Analysis. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Note discusses the results of stress testing of the banking sector and systemic risk analysis for New Zealand. The banking sector, which dominates the financial system, has significant exposure to real estate. A sharp decline in the real estate market, a prolonged period of low dairy prices, deterioration in global economic conditions, and a tightening in financial markets would adversely impact the system. Despite these risks, the banking system is resilient to severe shocks. Results of stress tests and sensitivity analysis indicate that the solvency and liquidity of the banking system can withstand adverse and severe shocks.